BEYOND THE PASTORAL: ENVIRONMENTAL IMAGINATION IN O.A BUSHNELL’S KA’A’AWA - Indriyanto, Kristiawan (Sanata Dharma University, 2020)
This paper explores the environmental imagination in O.A Bushnell’s Ka’a’awa through his representation of pastoralism. A Hawaiian novelist, Bushnell conceptualizes his idea of pastoral based on the Hawai’ians’ traumatic experience with the Western colonial powers. Different with the Anglo-American discourse of pastoralism which emphasizes more on the individual self and the reorientation toward the natural world in rural area, Bushnell foregrounds the far-reaching impact of colonialism which affects even the periphery of O’ahu island. The titular village of Ka’a’awa, previously a sacred place where the inhabitants with the blessing of Hawai’ian gods lived bountiful with nature also suffers the outbreak of Western diseases. Instead of a place for reorientation and rejuvenation, Bushnell’s concept of pastoralism in Ka’a’awa evoke the traumatic experience of the islanders in which the picturesque landscape of Hawai’i represents the silent witness towards the desolation of Hawai’ian archipelago. To reiterate, this paper argues how Bushnell orients his work within the socio-historical background of Hawai’i and deliver a critique towards the impact of colonialism towards the islanders through his conception of pastoral.